Masyarakat Rungus dan alambina di Tinangol, Kudat, Sabah - 461854 Lee, Anthony Cheng Huat (Sekudai : UTM, 1979)
This dissertation has locked at the relationship between activity, culture and physical design of the Rungus people, an indigenous sub-group of the Kadazan race in Sabah. The data obtained show that physical design factors which support cultural norms are the extremely important ones which influence user satisfaction with built environment. A systematic approache, observation and analysis of the behaviour components underpinning the activity of the people are done and a procedure of gathering the cultural-psychological data is also taken. Part one of this study, has looked into the Rungus household in relation to their way of life. This covers the role of each member of the family in their daily activities and seeks to dermine how this affect the form of their dwelling. In part two, the setting of the village community is considered in which the people's way of life is determined to see how it is reflected in the nature of their built environment of the village. The physical aspect of the design of their houses - the long house - is emphasized in the last part of the study and this has looked into the philosophical as well as the technical aspects of the Rungus house that are expressed in their built environment. To conclude, a brief discussion is done on the significant changes in their traditional socio-culture, and an attempt is also made in recommending the level of the development for the Rungus people. The study of this indigenous architecture which formed the backbone of this dissertartion has produced some general considerations for a better understanding on the modes of the interrelatedness between man and his built environment. The fundamental virtue of this study may hope to meet the architectcts' demand for more information, and that their creative potential makes the architect aware of the demarcation line between the expression of his value and meeting the real need of human requirements especially the cultural ones.